2018
DOI: 10.1002/2017gc006927
|View full text |Cite
|
Sign up to set email alerts
|

Holocene Paleointensity of the Island of Hawai `i From Glassy Volcanics

Abstract: This study presents new high‐quality paleointensity records and 14C radiocarbon age determinations from the Island of Hawai `i during the Holocene. Previous studies on Hawai `i use experimental methods and statistical selection criteria that may produce inaccurate geomagnetic field strength estimates. Additional high‐quality paleointensity results can be used to evaluate the existing Hawaiian data set and investigate Holocene geomagnetic field behavior. New paleointensity sites from 22 lava flows were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 72 publications
(252 reference statements)
4
28
0
Order By: Relevance
“…Cromwell et al (2015) demonstrated its robustness by reanalyzing the original measurement-level data obtained from the Kilauea 1960 lava by Yamamoto et al (2003) with the CCRIT and observed an improvement of the site mean from 49.0 ± 9.6 µT (N = 17) to 39.1 ± 5.0 µT (N = 8), which is reasonably consistent with the expected field intensity of 36.2 µT. Cromwell et al (2017) recently obtained 22 new site-mean paleointensities by the IZZI Thellier method with the CCRIT from newly collected glassy volcanic materials from Holocene surface lavas on the island of Hawaii. They compared these data to the previously published data based on cumulative distribution function (CDF) diagrams together with six sitemean paleointensities of the same quality that were obtained from historical surface lavas on the island of Hawaii by Cromwell et al (2015).…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…Cromwell et al (2015) demonstrated its robustness by reanalyzing the original measurement-level data obtained from the Kilauea 1960 lava by Yamamoto et al (2003) with the CCRIT and observed an improvement of the site mean from 49.0 ± 9.6 µT (N = 17) to 39.1 ± 5.0 µT (N = 8), which is reasonably consistent with the expected field intensity of 36.2 µT. Cromwell et al (2017) recently obtained 22 new site-mean paleointensities by the IZZI Thellier method with the CCRIT from newly collected glassy volcanic materials from Holocene surface lavas on the island of Hawaii. They compared these data to the previously published data based on cumulative distribution function (CDF) diagrams together with six sitemean paleointensities of the same quality that were obtained from historical surface lavas on the island of Hawaii by Cromwell et al (2015).…”
Section: Introductionmentioning
confidence: 53%
“…As reviewed in section Introduction, Cromwell et al (2017) found that the CDF curve of the IZZI dataset (median of 43.5 µT, N = 28) was shifted to lower paleointensity values than those of the published Thellier-type data (median of 54.5 µT, N = 74) for the Holocene. Because the IZZI dataset was obtained by the modern technique and the stringent criteria, paleointensity in Hawaii during Holocene is thought to be more reliably characterized by the IZZI dataset.…”
Section: Holocene Paleointensity Variation In Hawaiimentioning
confidence: 83%
See 3 more Smart Citations